METAMEMORY AMONG SIGHTED AND NON-SIGHTED INDIVIDUALS. - Al-Jarrah, Abdelnaser; Al-Shreffen, Ahmad; Al Mehlej, Tamara (International Journal of Psychosocial Rehabilitation, 2021)
The purpose of this study was to examine the level of metamemory amongsighted and non-sighted individuals, and to find the difference between them accordingto their gender. We used Troyer and Rich’s Meta-Memory Scale to assess meta-memorylevels among groups of sighted and non-sighted individuals in Jordan. Two hundred anfifty individuals’ participants in this study, 99 participants were non-sighted (50 males,49 females). The study results showed that Strategies sub-scale was in the first order(medium level) for both sighted and non-sighted students. In the second order was thecontentment sub-scale. The ability sub-scale was last (low level). Non-sightedindividuals' mean on the strategies sub-scale was significantly higher than for sightedpeople. While there was no difference between the mean scores of sighted non-sightedgroups on the contentment and ability sub-scales, neither, there were any differencesbetween males and females on the three sub-scales. The study highlights the need toempower sighted and non-sighted to use different memory strategies.